Characterization of New Particle Formation in Soft X-ray Radiolysis Reactor: AMCs-to-Secondary Inorganic Aerosols - Jiyoon Shin; Kyungil Cho; Yoonkyeong Ha; Giwon Kang; Jihye Park; Hunkwan Park; Changhyuk Kim (Aerosol and Air Quality Research)
Abstract Airborne molecular contaminants (AMCs) in cleanrooms should be monitored and controlled tightly to reduce yield loss since they can be converted into nanoparticles or surface haze contamination on semiconductor chips or masks. Soft X-ray radiolysis was developed to detect AMCs as low as the ppt-level by forming secondary aerosols from AMCs under soft X-ray irradiation. However, new particle formation (NPF) using soft X-ray radiolysis has not been well investigated. In this study, we have developed a continuous flow tube reactor to understand NPF from AMCs using soft X-ray radiolysis. The reactor was designed to continuously maintain parabolic laminar flows within the tube reactor and to extend the exposure time of the gas molecules to soft X-rays by increasing the number of reactor modules. With the increase in the concentration of sulfur dioxide (SO2), the size distribution of particles formed by soft X-ray radiolysis also showed enhanced NPF and subsequent particle growth. However, the conversion rates of SO2 into particles decreased simultaneously. The NPF and subsequent particle growth in the reactor were also positively affected by the exposure time to soft X-rays and the residence time. The exposure time was controlled by the number of soft X-ray emitters, and the residence time in the reactor was adjusted by the number of reactor modules and the inlet flow rate. The mixture of ammonia (NH3) with SO2 stabilized the nucleation of particles formed from SO2 but suppressed the particle growth. In contrast, nitrogen dioxide (NO2) suppressed both nucleation and growth of particles formed from SO2. Among the parameters for controlling soft X-ray radiolysis, the soft X-ray intensity had the highest effect on the inorganic AMCs-to-nanoparticle conversion.